APLIKASI MEDIA PEMBELAJARAN INTERAKTIF SISTEM PANCA INDERA MANUSIA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY UNTUK SISWA SMP - Ihsanul Ulia, Rifa; Fajar Rodiansyah, Sandi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Natural Sciences (IPA) is one of the subjects taught at the junior high school level. By using the lecture method, describing it on the board, or just looking at it in a textbook, it creates difficulties for most students in understanding the material. Factors causing difficulties in understanding students are due to the lack of visualization of real objects from the material presented. This raises a sense of laziness and saturation towards students in learning the five senses which is one of the sub-material found in junior high school science subjects. To overcome the problems mentioned above, the writer tries to compile a study entitled "Application of Learning Media for Human Sensory Systems Using Augmented Reality Technology for Junior High School Students". The author hopes that by designing this application, it will attract students' interest in learning the five senses and students can directly observe the three-dimensional object of the five senses.